Use of The Canva Application to Develop LKPD Based on CTL in Geometry in Mathematics Subject - Cindi Safitra Saragih; Muhammad Amin Fauzi; Wildansyah Lubis (Randwick International of Education and Linguistics Science Journal, 2024)
Mathematics is a basic science that has a very important influence on life, because mathematics can prepare and develop students' abilities to think logically, flexibly and precisely to solve problems in their daily lives. This research is research into the development of mathematics worksheet for elementary school students. The aims of this research were to 1) determine the validity of CTL-based LKPD on cube and block materials; 2) find out the practicality of CTL-based LKPD on cube and block materials; and 3) determine the effectiveness of CTL-based LKPD on cube and block materials. This research was conducted at SD Negeri 101964 Jaharun A with research subjects namely 25 class V students. The validators in this research consisted of material experts, media experts and language experts. Teachers and students as product users test the practicality of CTL-based LKPD. This type of research is research and development with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The research instruments used were interviews, validation sheets, teacher and student response questionnaires, as well as test instruments in the form of test essays. The data collection techniques in this research are interviews and tests, with data analysis techniques for testing validity, level of difficulty, distinguishing power, and reliability for test instruments, and n-gain tests. The results of this research show that the CTL-based LKPD is declared feasible because it meets the criteria of being valid, practical and effective for use in teaching mathematics regarding cubes and blocks.